Emotional intelligence, self-regulated learning, and academic achievement in technology-mediated learning: a systematic literature review - Nazara, Rangga Gustiawan; Wardani, Ella Kusuma; Fatimah , Waode Sitti; Hidayati, Wiwik (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2025)
This study aims to synthesize empirical evidence on the role of emotional intelligence (EI) in supporting academic achievement within technology-mediated learning environments, addressing the current gap in fragmented findings and the lack of comprehensive reviews connecting EI with digital learning demands. Using the PRISMA 2020 protocol, a systematic literature review was conducted across Scopus, Web of Science, ERIC, and Google Scholar, covering empirical studies published between 2014–2024. From an initial pool of 500 records, 15 studies met the inclusion criteria and were analyzed thematically, with meta-analytic insights incorporated where effect-size data were available. The results indicate that EI enhances academic performance by strengthening self-regulated learning, motivation, emotional regulation, and collaborative engagement across online, blended, and asynchronous modalities. Challenges include inequitable digital access, insufficient teacher preparedness, and cultural constraints on emotional expression. The review contributes theoretically by proposing an integrated understanding of EI as both a cognitive facilitator and an affective buffer in digital learning ecosystems, highlighting its relevance for instructional design, teacher training, and policy development.